2021
DOI: 10.3390/sym13081478
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Force Analysis of Adjacent Shield Tunnel Caused by Foundation Pit Excavation Considering Deformation of Retaining Structures

Abstract: In order to research the theory for the variety of transverse forces of the adjacent shield tunnels caused by foundation pits excavation, the effect mechanism of foundation pit excavation on the adjacent shield tunnel was analyzed. The sidewall unloading model of the foundation pit, considering the deformation of the retaining structures, was introduced to calculate the additional stress of soil caused by foundation pit excavation. On this basis, the additional confining pressure variation model of the adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The unequal displacement of the upright column would result in the differential displacement of the supporting system on the vertical plane and the plane, which would ultimately result in the secondary stress of the supporting axial force [27][28][29][30]. If there was a significant settlement between the upright column and the retaining wall or between the upright column and the retaining wall, it would result in eccentric compression or even instability of the supporting system, thereby causing an engineering accident; therefore, the vertical displacement of the column was crucial to the stability of the foundation pit enclosure system.…”
Section: Analysis Of Upright Column Simulation Resultsmentioning
confidence: 99%
“…The unequal displacement of the upright column would result in the differential displacement of the supporting system on the vertical plane and the plane, which would ultimately result in the secondary stress of the supporting axial force [27][28][29][30]. If there was a significant settlement between the upright column and the retaining wall or between the upright column and the retaining wall, it would result in eccentric compression or even instability of the supporting system, thereby causing an engineering accident; therefore, the vertical displacement of the column was crucial to the stability of the foundation pit enclosure system.…”
Section: Analysis Of Upright Column Simulation Resultsmentioning
confidence: 99%
“…Nevertheless, the construction process frequently encounters a challenge of adjacent foundation pits due to the scarcity of available land in urban areas [19]. Xinhai Zhang [20] et al considered factors such as deformation of the foundation pit support structure, distance between the tunnel and the foundation pit, and excavation depth of the foundation pit. They analyzed the confining pressure of the adjacent shield tunnel, the values of bending moment and shear force, and the axial force at the top and bottom of the tunnel's segment ring.…”
Section: Introductionmentioning
confidence: 99%
“…Pile-anchor systems are highly effective in controlling the deformation of large-scale excavations, while multi-level support systems can provide uniform support at different depths, and by optimizing the arrangement and timing of support layers, the overall soil deformation can be minimized [18,22]. Through numerical simulations and model experiments, comprehensive studies of key parameters such as soil deformation, stress distribution during pit excavation, displacement, shear forces, and moments of rail transit structures have been conducted [23][24][25]. For example, based on numerical simulations, Liao et al found that subway stations adjacent to deep excavations experience rotational and shear effects, potentially leading to structural fatigue and reduced safety [26].…”
Section: Introductionmentioning
confidence: 99%